Quantitative Trait Loci for Morphological Traits and their Association with Functional Genes in Raphanus sativus - Yu, Xiaona; Choi, Su Ryun; Dhandapani, Vignesh; Rameneni, Jana Jeevan; Li, Xiaonan; Pang, Wenxing; Lee, Ji-Young; Lim, Yong Pyo (Frontiers in Plant Science, 2016)
Identification of quantitative trait loci (QTLs) governing morphologically important traits enables to comprehend their potential genetic mechanisms in the genetic breeding program. The present study, we used 210 F2 populations derived from a cross between two inbred lines radish (Raphanus sativus) ‘835’ and ‘B2’, and detected QTLs for 11 morphological traits related to whole plant, leaf and root yield during three years replicated field test. Total fifty-five QTLs were detected, and they were distributed on each linkage group of the Raphanus genome. Individual QTLs accounted for 2.69–12.6 of the LOD value, and 0.82–16.25% of phenotypic variation. Several genomic regions affecting multiple traits were clustered together, suggesting the existence of pleiotropy linkage. Synteny analysis of the QTLs regions with A. thaliana genome sequences allowed selection of candidate genes at QTL cluster positions. The five identified auxin and gibberellin candidate gene-base markers co-localized with underlying QTLs affecting different traits. In addition, comparative QTL analysis with B. rapa revealed six common QTL regions and four key major evolutionarily conserved crucifer blocks (J, U, R, and W) harboring QTL for morphological traits. The QTL positions identified in this study will provide a resource for finding more functional genes when the impending full radish genome sequence is released. Candidate genes identified in this study through co-location to QTL regions are expected to facilitate improvements in radish breeding programs.